Making literature now - Hungerford, Amy (Post 45, 2016)
"This book takes us into the social networks of contemporary literary culture, examining how small-scale presses, writers, book distributors, and editors make new fiction-and make a living-in a mass market indifferent to all but a tiny slice of the literature produced today. McSweeney's, the small San Francisco-based press founded by Dave Eggers, is the book's central subject, but the story of that press serves also as portal to broader networks of contemporary literary production, a network that requires not one person-like the famous Eggers-but thousands. How does new writing emerge and find readers today? Why does one writer's work become famous while another's remains invisible? Making literature now tells the stories of the creators, editors, readers, and critics who make their living by making literature itself come alive. The book shows how various conditions--including gender, education, business dynamics, social networks, money, and the forces of literary tradition--affect the things we can choose, or refuse, to read. Amy Hungerford focuses her discussion on literary bestsellers as well as little-known traditional and digital literature from smaller presses, such as McSweeney's. She deftly matches the particular human stories of the makers with the impersonal structures through which literary reputation is made. Ranging from fine-grained ethnography to polemical argument, this book transforms our sense of how and why new literature appears--and disappears--in contemporary American culture"--